Designing Sustainable Environmental Education: Analyzing Indonesian Teachers' Needs Using MDS Rapfish - Mahmud Alpusari; Barokah, Rifqa Gusmida Syahrun; Anggriani, Mitha Dwi; Mulyani, Eva Astuti; Fatmawilda; Amenda, Arvinalde (Jurnal Pendidikan dan Pengajaran, 2025)
The implementation of EE in Indonesia faces various obstacles, including limited resources, lack of institutional support, and low teacher readiness. This study aims to design a sustainable environmental education model by analyzing the needs of teachers in Indonesia through a Multidimensional Scaling (MDS) approach. This study used the Rapid Appraisal for Sustainability (Rapfish) method with Multi-Dimensional Scaling (MDS) analysis. Data were collected through a questionnaire distributed to 20 randomly selected primary school teachers from various regions in Indonesia. The results of the analysis show that teachers see the potential of EE to improve students' awareness and behavior towards environmental issues, but they face various challenges, such as limited time allocation in the curriculum to deliver EE materials, as well as lack of support from schools and parents. The existing curriculum is considered to still need development, especially through practical activities outside the classroom to increase student engagement. The findings emphasize the importance of government and organizational support through the provision of resources, professional training and curriculum development that includes practical project-based activities. The implications of this research are expected to guide the design of a more effective EE curriculum for primary schools, in line with global sustainable development goals. In conclusion, sustainable environmental education in Indonesia requires more targeted and appropriate curriculum design and teacher training. The implications of this research encourage policy makers to formulate policies that strengthen the integration of environmental education in the national education system.